Comparison and Evaluation of the Low-Level Laser and the Red and Blue LED Effects on Wound Healing in Rabbit - Ghaemi, Marjan; Sharifi, Davood; Mokmeli, Soheila; Kowsari, Golshad; Mortazavi, Pejman; Golmai, Pouneh (Journal of Lasers in Medical Sciences, 2019)
Introduction: Wound healing is a dynamic, interactive process to achieve the restoration of skin integrity and proper function after damage. Applying a low-level laser (LLL) and light emitting diodes (henceforth LEDs) is introduced in previous studies to accelerate the process of wound healing. The aim of this study is to compare the effect of the LLL and LEDs on wound healing in rabbits. Methods: Full thickness same size square excision wounds were created on the dorsum of the rabbits. Twenty rabbits were randomly divided into four groups, according to the treatment received. Group 1: the AlGalInP (aluminium gallium indium phosphide) laser (4 J/cm²); group 2: the red LED (30 J/cm²); group 3: the blue LED (60 J/cm²) and group 4, as the control group, was not irradiated. After 30 days, the wounds were evaluated both morphologically and histopathologically. Statistical significance was defined as a P value of less than 0.05. Results: All interfering methods including the LLL and LEDs had better outcome compared with the control group of both sizes and histopathologic features. The red laser group showed better results compared to the control group and either the LED groups. Comparing LEDs, the red LED performed better than the blue LED. Conclusion: This study confirmed the significant effects of the LLL and LEDs on wound healing. Comparing the LLL and LED, the LED may be a better choice, especially for bedridden or debilitated patients. The LED may also more cost effective in wound healing in comparison with the LLL.